Analisis Getaran untuk Mengindentifikasi Gearmesh Pada Transmisi Roda Gigi Lurus Menggunakan Perangkat Lunak Labview - Eddy, Noor; Purabaya, VVibawa; Helson, Helson (MESIN, 2007)
Vibration Analysis to Identity Gearmesh on Spur Gears Transmission by UsingLabVIEW Software. Spectrum vibration analysis which is done and focus on gearmesh. In thisexperiment, transmission ofspur gears is employed which is completed by a double-rotors kit model as aload. This experiment, which is done by using two kinds oflubrication with different viscosity such asSAE 20W-50 and SAE 15W-50. Vibration analysis employs alternative software, Lab VIEW that has highsimplicity andflexibility in making the customization as necessary. LabVIEW may be used to monitor themachine condition continuously and to acquire data when needed. Thus, the characteristic vibrationanalysis may be observed and ifan abnormal condition takes place, the solution may be required.